Peningkatan Pemahaman dan Keaktifan Siswa Kelas V SDN Kalibening Tahun Pelajaran 2017/2018 dengan Model Pembelajaran STAD - Alusia Budiasih; Warnesih Warnesih (Educational Consultant & Counseling Career (EC3) Mataram, 2021)
The purpose of this study was to increase students' understanding and activeness in science subjects on light material using the STAD model. The type of research used is Classroom Action Research (CAR) which is carried out through III cycles. The research subjects were 15 students of class V of SD Kalibening Kecamatan Dukun Kabupaten Magelang consisting of 9 male students and 6 female students, conducted in the even semester of the 2017/2018 academic year in April. Data collection techniques include observation sheets and test sheets during the action and documentation of learning activities. The results of data analysis showed an increase in student activity in learning from cycle I was quite good, increased to good in cycle II, and increased to very good in cycle III. The results of research using the STAD method have been able to increase students' understanding and activeness even though they have not been maximized. This success is supported by the readiness of teachers in designing learning and learning processes that are carried out according to plan. However, there are still main factors that are felt to be inhibiting, namely not all students are able to work in groups. Therefore, researchers must often train students in group work and make interrogative sentences that help them understand the material.